Visible-light-driven Z-scheme rGO/Bi2S3–BiOBr heterojunctions with tunable exposed BiOBr (102) facets for efficient synchronous photocatalytic degradation of 2-nitrophenol and Cr(vi) reduction. Issue 12 (5th November 2019) - Li, Hui; Deng, Fang; Zheng, Yang; Hua, Li; Qu, Chunhua; Luo, Xubiao
Abstract : Fabrication of Z-scheme heterojunctions and crystal facet engineering are effective strategies for enhancing visible-light photocatalytic redox ability. Abstract : Fabrication of Z-scheme heterojunctions and crystal facet engineering are effective strategies for enhancing visible-light photocatalytic redox ability. Visible-light-responsive Z-scheme reduced graphene oxide (rGO)/Bi2 S3 –BiOBr heterojunctions with a tunable exposed BiOBr (102) facet and high stability were prepared by a one-pot solvothermal strategy. A graphene oxide (GO) solution acts as a rGO precursor and crystal facet controlling agent of BiOBr (102). The optimized 1% rGO/Bi2 S3 –BiOBr catalyst shows a much higher photocatalytic activity in degrading a single-component 2-nitrophenol (2NP) solution and a reducing single-component Cr(vi ) solution than Bi2 S3, BiOBr and Bi2 S3 –BiOBr. In the mixture solution of 2NP and Cr(vi ), 2NP degradation and Cr(vi ) reduction occur simultaneously, and the Cr(vi ) reduction efficiency and 2NP degradation efficiency reached 95% and 67%, respectively. The synergism of rGO/Bi2 S3 –BiOBr for simultaneous 2NP degradation and Cr(vi ) reduction can be attributed to the efficient production of electrons and reactive oxygen species. This work sheds light on the design of facet-dependent Z-scheme photocatalysts to advance photocatalytic redox capability.